ANALISIS KAPASITAS FISKAL DAN PENGARUHNYATERHADAP ANGGARAN BELANJA MODAL PADA PEMERINTAH DAERAH DI SUMATERA - Vince Ratnawati, Liza Fiona, Taufeni Taufik, (Jurnal Ekonomi, 2016)
This study aims to determine the effect of Local Own Revenue, Revenue Sharing, General Allocation Funds, Other Local Revenues, and Personnel Expenditure affect the Capital Expenditure Budget District / City Government on the island of Sumatera. The population in this study is the district / city governments in Sumatra 2009-2013. By using purposive sampling method, of 151 regencies / cities in Sumatra obtained a sample of 122 district / city. This research is a quantitative research using secondary data. Testing the hypothesis in this study using multiple linear regression with t test, and the coefficient of determination. The results showed that the Local Own Revenue, Revenue   Sharing,   General   Allocation   Funds   significant   affect   Budget   Capital Expenditure, Other Local Revenue no effect on the Budget Capital Expenditure, while personnel expenditure have a significant effect but with a negative direction.